Fly fishing west Yellowstone : a history and guide - Staples, Bruce; Jacklin, Bob, 1945- (Stackpole Books, 2021)
"Fly-fishing legend Bob Jacklin and well-known writer and fly historian Bruce Staples team up to write the compelling history of this area, which still remains the epicenter of fly fishing in the western United States. This book also includes fly patterns, past and present, as well as up-to-date information about these famous rivers, making this an indispensable reference for anyone visiting the region"--